Assessing Strategies for Teaching Vocabulary and Developing Lexical Competence in Language Education - Ariremako Afolabi Innocent; Oladele Jiboku; Gladys N. Kefas (Britain International for Academic Research (BIAR-Publisher), 2025)
This study investigates the role of vocabulary in language teaching syllabus through the lenses of Cognitive Linguistics, Sociocultural Theory, and Usage-Based Linguistics. Vocabulary is central to language acquisition, yet limited lexical knowledge often leads to learner frustration and demotivation. Despite vocabulary’s centrality to language acquisition, it is often underemphasized in curricula, leaving educators with limited guidance on effective instruction (Berne & Blachowicz, 2008). Using a qualitative approach, classroom observations, teacher interviews, and curriculum analysis, the research explores how vocabulary is addressed in instructional practices and identifies challenges such as pedagogical inconsistency and teacher uncertainty. Grounded in theories that emphasize mental representation, social interaction, and meaningful use, the study reveals a gap between theoretical models and classroom implementation. Findings underscore the need for professional development and curriculum reform that elevate vocabulary instruction as a core component of language education.